NOSOCOMIAL INFECTIONS: ANALYSIS OF NATIONAL AND GLOBAL EXPERIENCE (International journal of medical sciences, 2025)
Hospital-acquired infections (HAIs) remain one of the most significant healthcare problems, significantly impacting morbidity, mortality, and the economic costs of healthcare facilities. This article presents a comparative review of national and global practices in the prevention and control of HAIs, focusing on current epidemiological trends, risk factors, and common etiologic agents. Particular attention is paid to an analytical study of the situation in Uzbekistan and a comparison with international standards, including recommendations from the WHO, CDC, and European Centers for Infection Control. Successful practices in developed countries, such as the introduction of care bundles, enhanced microbiological monitoring, and programs for the rational use of antibiotics, are analyzed. Based on the identified differences, key areas for improving infection control in healthcare facilities in Uzbekistan are identified. The review emphasizes the need for a comprehensive approach combining clinical, managerial, and educational measures to effectively reduce HAIs.